The outlook for the laborer - Anderson, William Aaron (My University, 1891)
Introduction: From earliest times there have always been at least two classes of people in a community; those that were compelled to labor, and those controlling the labor. The class which exerted the control were also laborers in a certain sense, though their labor was not operative, but executive and and speculative, according to the classification of labor by President Fairchild. The strongest ruled. He who could subjected others and compelled them to labor to his advantage. Much the same condition exists today, though instead of Kings and lords ruling over serfs, we have the capitalist dictating to the laborer. In modern times the quality of strength in arms has become unnecessary to the control of labor. Civilization makes it possible for a few, stronger in mind than their fellows to accumulate wealth with safety. This wealth used in the production of more wealth has become of late years a power perfectly appalling in its ability to both affect the finances of nations and reduce the poorer class to a condition of practical servitude.
Citation: Anderson, William Aaron. The outlook for the laborer. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Labor; Social structure; Capitalism; Theses; Manuscripts (documents)